Importância do desenho infantil para o desenvolvimento da escrita na vida escolar - Lima, Andréa Morassutti (Universidade Federal de São Carlos, 2024)
The present work constitutes a bibliographical research with the objective of analyzing, in scientific production in the area of ​​education, the importance of children's drawings, created in the classroom, in order to understand their relevance as a precursor to writing. From a young age, children are encouraged to draw, but when they move on to Elementary School this practice is no longer highlighted as a means of starting literacy. So, what is the relationship between children's drawing and writing? What practices related to teaching and learning writing from drawing can we develop in the classroom? And what is the educational and personal importance of drawing and writing for children? To answer these questions, this Course Conclusion Work will be based on authors such as Magda Soares (to support concepts such as literacy and literacy), Emília Ferreira (focusing on the evolution of writing) and Lev Vygotski (who brings contributions to the field of design). Research collection began in November 2022 and it was decided to use online databases such as the Brazilian Digital Library of Theses and Dissertations (BDTD), the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel ( CAPES), Sucupira Platform and Google Scholar. Thus, it is concluded that if there is intentionality and systematic work on the part of the teacher, drawings can be rich instruments towards the child's appropriation of writing.
Importance of children's drawing for the development of writing in school life
Keywords: Alfabetização; Desenho infantil; Escrita; Literacy; Childish drawing; Writing; CIENCIAS HUMANAS::EDUCACAO::CURRICULO